SIP in China How Privatization Affect Firm Financial and Operating Performance? - Wang, Yu (2004)
Privatization program in China has attracted the world attention because of its special economic and political contexts, and its different strategy. Share issue privatization (SIP) is a practical and powerful approach used in this program. An insight of SIP will help people to gain a better understanding of the whole privatizing program. This paper compares financial and operating performance of a sample of 100 firms before and after privatization. I find mixed results of SIP. Measures that improve following privatization include operating efficiency, capital investment spending, and output; employment level increases and leverage significantly declines. Meanwhile, most SIP firms experienced a sharp (and also significant) decrease in profitability ratio measures.